Empowering Voices: Breaking the Silence of Speaking Anxiety Among Pesantren Students - Hilma Adzkia; Ahmad Syafi'i; Juniar Frida Andini (STKIP AL HIKMAH SURABAYA, 2023)
Self-esteem and confidence may be the most common causes of speaking anxiety in the English classroom. Most students never feel completely confident when speaking in a foreign language class. They also believe that their classmates are better at languages than they are. Furthermore, they would not respond voluntarily in foreign language class because it would be embarrassing for them. The students were also concerned about falling behind in language class because it moved so quickly. As a result, they were more tense and nervous in language class than in any of my other classes. They also became nervous and confused while speaking in language class. They also became anxious when they did not understand everything the language teacher said. Similarly, they were overwhelmed by the number of rules they needed to learn in order to speak a foreign language.